“Tuberculosis”: A Surprise Guest in Carcinoma of Pinna - Aroor, Rajeshwary; Bhat, Vadisha Srinivas; Koikkara, Remya; Abdulrahim, Razna; Rajendra, Vinay Kumar J.; Laxminarayana, Kishan Prasad H. (Journal of Health and Allied Sciences NU, 2021)
Tuberculosis is a common health care problem worldwide, though the incidence has come down in recent years due to various health care programs targeting tuberculosis and improved living conditions. Cervical lymph nodes are among the common sites for extrapulmonary tuberculosis. They usually present with painless enlargement of cervical lymph nodes with or without constitutional symptoms. Tuberculosis rarely coexists with malignancy in the geographical area where the prevalence of tuberculosis is high. The disease needs to be treated with antituberculosis treatment as per standard guidelines and the primary treatment of malignancy. We report a case of an adult male presented with a lesion on the pinna, which was diagnosed as squamous cell carcinoma of the pinna on biopsy; he was later found to have coexistent tuberculosis after undergoing surgery for carcinoma.
Keywords: tuberculosis; squamous cell carcinoma; pinna; cervical lymph node; antituberculosis treatment